Penguasaan Kompetensi Pedagogik Guru Bahasa Indonesia dalam Menerapkan Keterampilan Membuka dan Menutup Pembelajaran pada Materi Teks Debat di SMA - Sandi, Andre Taulani; Haryanti, Yeni; Gusfika, Ongky; Noermanzah, Noermanzah; Suryadi, Suryadi (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2022)
The pedagogical competence of Indonesian language teachers will influence student learning outcomes and whether or not learning objectives are achieved. One of the pedagogic competencies that must be mastered by Indonesian language teachers is the skill of opening and closing lessons. For this reason, the purpose of this study was to describe the mastery of Indonesian language teacher pedagogic competencies in applying the skills of opening and closing learning on the material for writing debate texts in class X SMA Negeri 6 Bengkulu City. The research method used is the qualitative content analysis method of the Mayring model. Data collection techniques use documentation techniques with the help of camcorders. The research data analyzed is speech in the process of learning to write debate texts. The data analysis step uses Mayring's model content analysis combined with the interpretation of the meaning of the Dell Hymes SPEAKING model. The results of the study showed that the Indonesian teacher's opening skills for learning started with greetings, praying, and checking physical attendance, while the skills for closing learning started with learning evaluation and greeting. From the results of this study it can be recommended to Indonesian teachers that in opening learning it must consist of the skills of saying greetings, praying, checking students' physical and psychological presence, giving apperception, conveying basic competencies and learning objectives to be achieved, while closing skills must consist of for the skills of providing conclusions in learning, providing evaluations in learning, providing motivation to students, providing follow-up, praying, and finally greeting and saying thank you.